The Influence Of Flash Card Toward Students’ English Vocabulary Mastery During Covid-19 - Hermansyah, Hermansyah; Nurhendi, Nurhendi (CV RIFAINSTITUT, 2021)
The purpose of this research is to see how flash cards influence the students' English vocabulary mastery. The researchers of this research used quantitative research methods with posttest only control design of true experimental design. The random sampling method was employed in this research's sampling. The data collected in this research was put to the test (multiple choice test). The researchers of this research gave different treatments for the experimental and control groups. The treatment for the experimental group was learning English with flash card media and the treatment for the control group was learning English conventionally. After the two sample groups were given different treatment, the two sample groups were each given a posttest with an instrument consisting of 20 multiple-choice questions with 4 alternative answer choices that had been tested beforehand and validated empirically. Analysis of research data is descriptive and inferential, which inferentially uses the t test, by first testing the assumptions of data normality and homogeneity of variance. The results showed that flash cards had an influence on students' English vocabulary mastery. Therefore, it can be said that this research has proved that there was a significant result of using Flash Cards towards children's English vocabulary mastery.